Pharmaceutical Considerations of Nasal In-Situ Gel As A Drug Delivery System - Khatri, Upasana; Saini, Sunil; Bharkatiya, Meenakshi (Asian Journal of Pharmaceutical Research and Development, 2021)
In situ gelling drug delivery systems have gained enormous attention over the last decade. They are in a sol-state before administration, and they are capable of forming gels in response to different endogenous stimuli, such as temperature increase, pH change and the presence of ions. Such systems can be administered through different routes, to achieve local or systemic drug delivery and can also be successfully used as vehicles for drug-loaded nano- and microparticles. Natural, synthetic and/or semi-synthetic polymers with in situ gelling behaviour can be used alone, or in combination, for the preparation of such systems; the association with mucoadhesive polymers is highly desirable in order to further prolong the residence time at the site of action/absorption. Nasal drug delivery is a better alternative of oral and parental route due to high permeability of Nasal epithelium, rapid drug absorption, avoid Hepatic first pass metabolism, increased bioavailability of drug, minimized local and systemic side effects, Low dose required, Direct transport into systemic circulation and CNS is also possible (passing blood brain barrier), Improved patient compliance, Self-Medication is Possible, prevent Gastro intestinal tract Ulceration. Recently, it has been shown that many drugs have better bioavailability by nasal route than the oral route. Thus, this review focuses on nasal drug delivery, various aspects of nasal anatomy and physiology, nasal absorption mechanism, advantages & disadvantage composition of in situ gel, application and In-situ gels evaluations.